COMPREHENSIVE ANALYSIS OF RAINFALL PROBABILITY IN PUNE DISTRICT, MAHARASHTRA - Nahire Dinesh J.1, Mane D.G. 2 & Sayyed Juned A. 3, (Chelonian Research Foundation, 2024)
Rainfall is the most effective and powerful component of our natural environment. These components have a complex bearing on the formation of soil, natural vegetation, different flora and fauna, biodiversity, and, ultimately, various economic activities and occupations of human beings. In this research work, an attempt is made to show how rainfall affects the various economic activities of a human being. The rainfall of the region plays an integral part in our natural environment. These elements influence the people's way of life in a particular region. Even the land's surface is primarily modified by the action of rainfall. In agricultural activity, planting crops requires an intelligent use of information about rainfall regarding the length and characteristics of the growing season. Thus, the available rainfall data are essential in agricultural activity, natural vegetation, biodiversity in flora and fauna, soil types, and climatic changes in the region. The analysis of rainfall explains the causal relationship between climate and human activity, which serves the primary purpose of this work. This research article thoroughly investigates the climatic dynamics of Pune District, Maharashtra, focusing on the analysis of historical data related to rainfall and the probability estimation of rainfall. The study aims to contribute valuable insights into the spatiotemporal patterns of these meteorological variables, providing a basis for informed decision-making in sectors such as agriculture and water resource management. Keywords: Analysis, Rainfall, Trends, Methodology, Probability Estimation